2016
DOI: 10.1185/03007995.2016.1171204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telmisartan on fat distribution: a meta-analysis of randomized controlled trials

Abstract: The findings suggest that telmisartan affected fat distribution, inducing visceral fat reduction, and thus could be useful in hypertensive patients with obesity/overweight, metabolic syndrome, or glucose intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
2
4
0
2
Order By: Relevance
“…Interestingly, ARBs, including telmisartan, have been shown to reduce body weight, as found in this study ( Fig. 1 B) and adipose tissue 35 , 36 and, furthermore, reduction of body weight and adipose tissue is associated with lowering of IOP. 37 , 38 However, the similarity of IOP responses to bead injection argues against IOP-mediated effects of weight loss or BP lowering as contributing to the observed neuroprotection.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, ARBs, including telmisartan, have been shown to reduce body weight, as found in this study ( Fig. 1 B) and adipose tissue 35 , 36 and, furthermore, reduction of body weight and adipose tissue is associated with lowering of IOP. 37 , 38 However, the similarity of IOP responses to bead injection argues against IOP-mediated effects of weight loss or BP lowering as contributing to the observed neuroprotection.…”
Section: Discussionsupporting
confidence: 78%
“…The pharmacological actions of telmisartan did not influence by the gender (26). The possible explanation of the effect of telmisartan on the waist circumference is telmisartan induced changes in the fat distribution, and thereby it reduced the visceral obesity (27). Placebo-treated patients showed a significant improvement in the lipid profile, which can be attributed to the diet modifying regimen.…”
Section: Discussionmentioning
confidence: 88%
“…A limited meta-analysis of three RCTs 83 with telmisartan treatment duration of 16-24 weeks (combined sample size of 62 participants) showed that telmisartan caused a significant reduction in visceral, but not in subcutaneous, fat suggesting a beneficial effect on body fat. However, the current study did not observe any significant reduction in internal visceral fat with any of the telmisartan doses over a period of 24 weeks.…”
Section: Telmisartan Significantly Reduced Liver Fat But Not Total Bmentioning
confidence: 99%